Characteristic of urethral microbiota of men with idiopathic urethritis - Vorobiei, Yelizaveta; Skliar, Tetyana; Zubareva, Inna (ScienceRise: Biological Science, 2020)
Aim: to study the urethral microbiota composition in urogenital infections in men and to determine the sensitivity of isolated microorganisms to antibacterial drugs. Materials and Methods. 957 samples of biological material from the urethra of men were examined. The identification of the microorganisms was carried out according to the Bergey’s Manual of Systematic Bacteriology. Sensitivity to antibiotics was determined by the disco-diffusion method, using standard disks of industrial production in accordance with the order of the Ministry of Health of Ukraine No. 167 of 05.04.2007. The mathematical processing of the results was performed, using the computer program " Origin Pro 7.0". Results of the research. According to the study, the presence of conditionally pathogenic microorganisms was found in 716 people (74.82% of the total number of the surveyed contingent). Of the subjects studied, 1574 strains were isolated, of which the vast majority consisted of bacteria of the intestinal group (43.52%) and staphylococci (32.46%). The incidence of streptococci was 18.61%, corynebacteria - 3.81%, pseudomonads - 1.14%, candida - 0.44%. When studying the species composition of urethral microbiota, the presence of monoinfection was found in 267 people, in the other 449 persons different associations of representatives of conditionally pathogenic microbiota were detected. The analysis of the level of sensitivity of the studied strains to antibiotics showed that the isolated staphylococci showed the highest sensitivity to ampicillin / sulbactam (81.60% sensitive strains), most cephalosporins (79,26 ± 4,49%), carbapenems (93,35 ± 1,38 %), vancomycin (100%), rifampicin (92.56%), most fluoroquinolones (82.68 ± 3.31%) and linezolid (98.63). Whereas the highest number of susceptible strains of bacteria of the intestinal group was determined for carbapenems (89.64 ± 2.68%) and Co-trimoxazole (82.19%). Conclusions. Isolated bacterial strains of the intestinal group and staphylococci are most commonly found in association with other microorganisms. The analysis of the level of antibiotic sensitivity indicates that staphylococci showed the highest sensitivity to ampicillin / sulbactam, most cephalosporins, carbapenems, vancomycin, rifampicin, most aminoglycosides and linezolid. Whereas the highest number of susceptible strains of bacteria of the intestinal group was determined for carbapenems and Co-trimoxazole. Which makes the use of these antibiotics appropriate for the treatment of diseases of the men’s genitourinary system